PERAN GURU TAHFIDZ DALAM MENGUATKAN HAFALAN SANTRI DI PONDOK PESANTREN DARUSY SYAHADAH UNIT KULLIYATUL MU’ALLIMAT LITTAHFIDZIL (KMT) QUR’AN BOYOLALI - Fauzah Nur 'Aini; Hidayatul Chasanah; Muhammad Isa Anshory (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
Memorization of the Qur'an at Pondok Pesantren Darusy Syahadah, Unit Kulliyatul Mu’allimat Littahfidzil Qur’an Boyolali. This study employed a qualitative descriptive approach, with data collected through in-depth interviews, observation, and documentation. Research subjects included the unit head, tahfidz teachers (muhafidzah), and students (santri). The results indicate that tahfidz teachers serve as guides, motivators, evaluators, and monitors of students’ memorization progress. The tahfidz program is carried out in a structured manner through three daily halaqah sessions, group and individual muraja'ah, and periodic evaluations through MHQ (Musabaqah Hifdzil Qur’an) and tasmi’. Memorization reinforcement strategies include intensive repetition, use of mutaba’ah books, Ramadan tahfidz quarantine, and motivational programs such as Farhah bil Qur’an and takrim muthalibat. The main obstacle encountered is the lack of discipline among some students in conducting ziyadah and muraja’ah. Student success in memorization is measured not only by the quantity of verses memorized, but also by the ability to maintain consistency.